MODEL PENGELOLAAN KOMUNIKASI BERBASIS PEMBERDAYAAN EKONOMI DI KAWASAN PARIWISATA RUPAT UTARA - Nurjanah Nurjanah; Muhammad Firdaus; Samsir Samsir; Rusmadi Awza (Jurnal Riset Komunikasi (JURKOM), 2020)
The growth of the tourism industry has created social, economic, and environmental changes, so management steps are needed. Not only from the government but requires community involvement, both local and regional. North Rupat has various tourism potentials that can be managed in synergy to advance the strength and economic welfare of the community independently. The purpose of this research is to explore, find, and describe a model of communication management in community economic empowerment. This study uses a qualitative method. Data collection techniques through interviews with 10 informants, observation, FGD, and documentation. The research results show that an integrated management model through the control and management of communication resources in various forms of effective communication can improve the community's economy independently. Management of communication through various communication resources by planning, organizing, implementing and controlling communication elements in achieving predetermined goals. Meanwhile, the form of communication in achieving goals is adjusted to the character of the local community, through socialization, assistance, and counseling using information media and technology.